Women’s Stereotypes in the Novel Perempuan Bayangan: A Structural Approach Study - Jeprayana Jeprayana; Vebbi Andra; Wenny Aulia Sari (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
This research was aimed to describe the intrinsic elements and the stereotypes of women found in the main characters of the novel Perempuan Bayangan by Netty Virgiantini. This research was designed by using a qualitative approach and content analysis method. In this research, the researchers implemented documentation techniques (literature study) in collecting the data of this research. Moreover, the interactive framework was used as the data analysis technique. The result of this research revealed that the intrinsic elements found in the novel included the theme (the eternity of love), characters, and the characterization. The characters and characterization consisted of the major characters, the supporting characters, and the shadow characters. The major characters were Ningrum, Satria and Padmi. The supporting characters were Ponco, Pandu, Pratiwi, Mrs. Sinta, Kokok, Tia, Satria’s mother and Ningrum’s mother. The shadow character was Utari. The setting of this novel included the Satria’s living room, pujahera, kitchen, boarding room, in the toast stall, restaurant, Ningrum's parents' house, office, sofa, the landlord's house. The setting of time included in the morning, evening, afternoon, and noon. The plot of the novel was chronological, and the points of views were first-person and third-person. The figure of speech included simile and oxymoron. Moreover, the moral values showed that one of the best ways in loving someone who died is by letting them go and praying for their peace in heaven, and never judge people at will by comparing them to the other ones as each person has its different strengths and weaknesses from each other. The woman’s stereotype found in the novel was that marriage was just based on personal benefits. The silence of women was considered as a sign of agreement on anything. Husband compared his wife to other women, and yelled at the wife whenever she was doing something.